Los límites territoriales de Buenos Aires durante la secesión: Apuntes sobre el debate constitucional de 1854 y la construcción del Estado bonaerense - Mariano J. Aramburo (Nuevo mundo - Mundos Nuevos, 2019)
In 1852 the Province of Buenos Aires rejected the agreement of San Nicolas and refused to participate in the constitutional process begun by the Argentine Confederation. Although it was considered part of the same Nation, Buenos Aires initiated an autonomous process of building State which was crystallized in 1854 with the ratification of its own Constitution. Therefore, replacing its political condition of province by that of State, reserving the exercise of its own sovereignty and declaring their territorial boundaries.The article studies the renewed interest of Buenos Aires’ ruling elite for the territory in those years. In particular, it analyses the debate on territorial limits in the Constitution of 1854, emphasizing the use of legal arguments and their relation to the defense of sovereignty and the construction of an autonomous State. In this sense, its hypothesis lies on the fact that the territory claimed by Buenos Aires was used as an element of dispute against the Argentine Confederation and that it expressed uncertainty as to the organization of the Nation.